AB0370 Peripheral Ulcerative Keratitis Associated with Autoimmune Diseases: Atypical Ocurrence in the Biologic Era. (9th June 2015) - García, M.; Garrido, G.; Ortiz, A.; Llorente, I.; Άlvaro-Gracia, J.M.; García de Vicuña, R.
Abstract : Background: Ocular inflammatory manifestations of autoimmune diseases include episcleritis, scleritis and peripheral ulcerative keratitis (PUK). RA is the leading cause of necrotizing scleritis and PUK, but Sjögren Syndrome (SS) is also a frequent underlying disease. These two ocular conditions can rapidly threaten ocular prognosis and are associated with increased mortality. Traditionally, this extra-articular complication has been described in patients with longstanding poorly controlled diseases, mainly RA. Objectives: To analyze the clinical profile and ocular outcomes of patients that presented with PUK in autoimmune diseases and their requirements of treatment. Methods: Retrospective non comparative observational study in patients with autoimmune diseases who developed a severe form of PUK. Demographic and clinical features, disease activity and therapy at PUK presentation, therapeutic requirements for PUK and response, recurrences and ocular complications were analyzed. Results: From September 2009 to September 2014, 8 patients (10 eyes) were included: 5 patients with RA, 1 patient with rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA) positive undifferentiated arthritis (UA), and 2 patients with Sjögren Syndrome (SS). Patient's characteristics are described in the Table below. The mean age at onset was 69, 37±5, 15 years and 75% were females. Two patients had bilateral involvement at PUK onset. The mean duration of underlying disease was 16±7.96 years. All patients were positive for RF and 75% (100% of RA) were ACPA +. At time of PUK diagnosis, 6 patients (75%) were under synthetic (s) and biologic (b) DMARDs (Table ), 1 was under low dose glucocorticoids (GC) only, and 1 was receiving no treatment. The median DAS28 in RA patients at PUK presentation was 3, 2 [1, 5-4, 5]. No clinical features of active systemic involvement besides PUK were present, and ocular infection was ruled out in all cases. The initial treatment in all patients was based on oral GC (1mg/kg/day), 5 of them in combination with intravenous (iv) cyclophosphamide (CYC) (at least 6 monthly doses). Azathioprine, cyclosporine A and RTX were prescribed in 3 additional patients (1 RA and 2 SS), respectively. Four eyes (4 patients) developed corneal perforation at PUK onset before immunosuppressive treatment was modified [m1] and 1 patient (1 eye) while he was under rituximab and iv CYC. Corneal transplant was required in 2 eyes. Mean time of response to immunosuppressive therapy was 8.06±5.63 weeks. Recurrences presented in 2 RA patients, both under iv CYP treatment. In both cases RTX, was added. To date, 1 of these patients has achieved remission but the second patient has experienced a new recurrence. Conclusions: In our small series of longstanding and seropositive RA or SS patients, most PUK episodes arose when remission, low or moderate disease activity was achieved with s or bDMARDs. These findings contrast with historically described data. RTX successfully controlled ocular vasculitis in one patient, but did not prevent a new recurrence in another. Contribution of bDMARDS can neither be suspected nor ruled out because of the study design and the size sample. More extensive populations should be recorded for definite conclusions. Disclosure of Interest: None declared